EXPERIÊNCIAS EM TÔRNO DA QUESTÃO DO GRAU DE MOAGEM, DA SOLUBILIDADE E DA AVALIAÇÃO DAS FARINHAS DE OSSOS - Brichta, Hans; Brichta, Manfred (REVISTA DE AGRICULTURA, 2015)
EXPERIÊNCIAS EM TÔRNO DA QUESTÃO DO GRAU DE MOAGEM, DA SOLUBILIDADE E DA AVALIAÇÃO DAS FARINHAS DE OSSOS